Library of the Museum of the Contemporary Art - Nastić, Olivera (Qualitative and Quantitative Methods in Libraries; Vol 4 No 1 (2015): March 2015 Issue, 2017)
The Museum of Contemporary Art in Belgrade (MoCAB) was opened on October 20th 1965. However, Museum activities began as early as 1958, when the institution of a Modern Gallery was formed with the purpose to oversee the development of contemporary art in Yugoslavia. After the construction of the new building was completed, the Council of the Modern Gallery gave a new name to the institution – the Museum of Contemporary Art.  The reasons for the foundation of the Museum were, in nutshell, these: to collect, research and display most valuable and distinctive works of Yugoslav art in the 20th century; to organize exhibitions of local and international contemporary art and to publish publications which would enable further examination and popularization of contemporary art; to systematically collect and classify documentation about modern and contemporary art; to explore new educational methods in the fields of visual culture, and theory and history of art. The founder and the first director of MoCAB Miodrag B. Protić developed the conception of the Museum based on analysis of the model of the Museum of Modern Art in New York. One of the important departments of the Museum in that respect was the Art Documentation Department. It consists of the library, hemerotheque, and photo documentation. Art documentation department gathers, prepares, categorizes and stores professional literature (book, catalogues, periodicals, and electronic editions), daily press, archive material and photo documentation from the field of visual arts, especially modern and contemporary international, Yugoslav and Serbian art. Thanks to the systematic gathering of material which followed the forming of various collections and the MoCAB exhibition activity, the department is now in possession of the finest and most complete documentation, including all the material about the artistic tendencies and the artists from the territory of exYugoslavia. Another assignment of the department is the preparation of all the necessary materials for exhibitions, catalogues and programs of MoCAB.